Effect of Problem‐Based Learning Combined With Rational Emotive Behavior Therapy on Psychological Outcomes, Self‐Efficacy, Adverse Events, Quality of Life, and Treatment Compliance in Breast Cancer Care: A Non‐Randomized Study. - Zhou, Yanru; Han, Yuanyuan; Jin, Runhao (Nursing & Health Sciences, 2026)
To evaluate the effectiveness of combined problem‐based learning (PBL) and rational emotive behavior therapy (REBT) on Psychological Outcomes, Self‐Efficacy, Adverse Events, Quality of Life, and Treatment Compliance in breast cancer care. In this non‐randomized study conducted at a tertiary hospital in China, 180 patients with breast cancer treated between October 2021 and August 2022 were divided into a control group (n = 90) receiving conventional education and a study group (n = 90) receiving PBL combined with REBT. Outcomes were assessed using validated scales including the Hamilton Anxiety/Depression Rating Scales, EORTC QLQ‐C30, General Self‐Efficacy Scale, a hospital‐designed compliance questionnaire, and adverse event follow‐up. After intervention, the study group demonstrated significantly greater improvements in psychological outcomes (p < 0.05), self‐efficacy (p < 0.05), lower adverse event rates (13.33% vs. 31.11%; p < 0.01), quality of life domains (p < 0.05), treatment compliance (p < 0.05), compared to the control group. The combined PBL and REBT approach enhances postoperative care for patients with breast cancer by improving psychological outcomes (e.g., reducing anxiety), enhancing self‐efficacy, minimizing adverse events, improving quality of life, and promoting treatment compliance. Key Points: This study fills a gap in the literature by demonstrating the combined application of problem‐based learning (PBL) and rational emotive behavior therapy (REBT) in breast cancer nursing, showing significant improvements in patient psychological outcomes (e.g., reduced anxiety and depression via HAMA/HAMD scores) and treatment adherence.The PBL + REBT approach enhances nurses' knowledge acquisition, skill development, and peer collaboration, providing practical strategies to elevate nursing education and breast cancer care practices.Combining PBL and REBT plays a crucial role in postoperative breast cancer care, reducing adverse events (from 31.11% to 13.33%), boosting quality of life (via EORTC QLQ‐C30), and increasing self‐efficacy (via GSES).